2015
DOI: 10.1080/21645515.2015.1095414
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal nasopharyngeal carriage in children <5  years of age visiting the pediatric emergency room in relation to PCV7 and PCV13 introduction in southern Israel

Abstract: The 7-valent and the 13-valent pneumococcal conjugate vaccines (PCV7 and PCV13, respectively) were introduced to the Israeli National Immunization plan in July 2009 and November 2010, respectively. Our aim was to assess pneumococcal conjugate vaccines (PCVs) uptake and dynamics in serotype-specific pneumococcal nasopharyngeal (NP) carriage in children <5 years old in southern Israel, during the immediate 5 y following PCV introduction. This was an ongoing, prospective, population-based, active surveillance, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 40 publications
1
48
2
Order By: Relevance
“…However, in previous studies that dealt with OM likely to be enriched with complex OM (the POETand COMPAS studies), no significant increase in non-VT disease was observed in vaccinated children [21]. Our group and others have shown an increase in non-VT pneumococcal nasopharyngeal carriage after PCV introduction [34,38]. In contrast, no such increase was shown in complex OM.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…However, in previous studies that dealt with OM likely to be enriched with complex OM (the POETand COMPAS studies), no significant increase in non-VT disease was observed in vaccinated children [21]. Our group and others have shown an increase in non-VT pneumococcal nasopharyngeal carriage after PCV introduction [34,38]. In contrast, no such increase was shown in complex OM.…”
Section: Discussionmentioning
confidence: 42%
“…This finding is important since in the crowded Bedouin population (in this aspect, resembling a developing-world population), PCV impact could, in theory, be delayed due to a higher carriage rate, starting from a very young age and expanding to older age, than in the Jewish population, resulting in higher exposure rates both to NTHi and S. pneumoniae [27][28][29][30][31][32]. We previously showed that PCV7/PCV13 reduced vaccine-type (VT) carriage in the 2 ethnic groups in a similar fashion, despite large differences in carriage rates [30,33,34]. Our results are therefore reassuring and suggest that in developing populations where chronic OM cases (including chronic suppurative OM and hearing loss) are prevalent [35], PCVs may prevent a sizeable proportion of the sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…12 Uptake of PCVs in southern Israel has been described previously. 10 A 2+1 PCV7 schedule (with doses administered at ages 2, 4, and 12 months) was introduced in July, 2009, with a catch-up campaign among children under 2 years of age. Beginning in November, 2010, PCV13 replaced PCV7 without additional catch-up.…”
Section: Settingmentioning
confidence: 99%
“…Previous pneumococcal vaccination (number of PCV7 and PCV13 doses) were ascertained from children's medical records. 10 Nasopharyngeal samples were obtained via dacron-tipped swabs and plated within 16 hours on 5% sheep blood/5.0µg gentamicin agar media, and incubated for 48 hours at 35ºC. Pneumococcal identification was based on alpha-hemolysis and optochin inhibition, and confirmed by slide agglutination.…”
Section: Surveillance Studymentioning
confidence: 99%
See 1 more Smart Citation